The influence of coaches’ instruction on technical actions, tactical behaviour, and external workload in football small-sided games - Batista, Jorge (2019)
Submitted by Bruno TRAVASSOS (bfrt@ubi.pt) on 2019-11-15T18:35:11Z No. of bitstreams: 1 2019_Batista_2019_coaches instruction in football.pdf: 278783 bytes, checksum: bc4b153dd82fbdc3b776fdd00fd7857b (MD5)